Evaluation of Antyhipercholesterolemic Effect of Allium cepa L. var cepa in Atherogenic Induced Rats - Lumban Gaol, Nurahmi; Yuandani; Sitorus, Panal (Indonesian Journal of Pharmaceutical and Clinical Research, 2021)
Fermented onion is a type of onion that produced by heating onion bulbs at high temperature for 15 days by fermenter machine. This research is expected to produce new alternatives therapy for reducing cholesterol from onions especially Allium cepa L. var cepa. In this experimental laboratory used 25 male white rats that divided into five groups, group I: negatif control, group II: positif control (Atorvastatin), group III: 100 mg/Kg body weight (bw) of fermented onion extact, group IV: 200 mg/Kg bw of fermented onion extract and group V: 300 mg/Kg bw of fermented onion extract. The Rats was feeding by an atherogenic diet to makes them hypercholesterolemia before treatment for 7th days, 14th days and 21st days. All of data were analyzed by ANOVA method (significant 0,05). The result concludes that of all the doses tested, fermented onion extract of Allium cepa L. var cepa with a dose of 200 mg/Kg bw has the highest effect in decreasing total cholesterol levels of hypercholesterolemia rats (Rattus novergicus).